Directions of artificial intelligence application in transport - Martynovych, Nataliia Oleksandrivna; Sundulov, Yevhen Henadiiovych (Golden Quill Publishing, 2025)
The report outlines key areas of application of artificial intelligence in the transport sector of Ukraine in the context of digital transformation. Their importance in the development of intelligent transport systems, automated monitoring and data analytics is proven. The practical potential of implementing solutions based on artificial intelligence to improve traffic safety, energy efficiency of transport and environmental sustainability of urban environments is substantiated. Their role in harmonizing Ukraine's transport policy with European standards and developing the concept of smart mobility is determined.

У тезах доповіді окреслено ключові напрями застосування штучного інтелекту в транспортній галузі України в контексті цифрової трансформації. Доведено їх значення у розвитку інтелектуальних транспортних систем, автоматизованого моніторингу та аналітики даних. Обґрунтовано практичний потенціал впровадження рішень на основі штучного інтелекту для підвищення безпеки руху, енергоефективності транспорту та екологічної стійкості міських середовищ. Визначено їх роль у гармонізації транспортної політики України з європейськими стандартами та розвитку концепції розумної мобільності.
Keywords: artificial intelligence; transport; sustainable development; management; projects; штучний інтелект; транспорт; сталий розвиток; управління; проєкти